Recurrent leg ulcers in a 16-year old Nigerian girl (2003)
This is a report of a 16-year old Nigerian girl who presented with recurrent leg ulcers associated with gastrointestinal symptoms. The management of this patient, who has ulcerative colitis manifesting with pyoderma gangrenous, underlines the need for thorough evaluation of cutaneous ulcers in the tropics. The medical treatment of ulcerative colitis in childhood, with reservation of bowel resection for complications is preferred.